Variation of T2 relaxation times in pediatric brain tumors and their effect on metabolite quantification. Issue 1 (26th April 2018) - Carlin, Dominic; Babourina‐Brooks, Ben; Davies, Nigel P.; Wilson, Martin; Peet, Andrew C.
Abstract : Background: Metabolite concentrations are fundamental biomarkers of disease and prognosis. Magnetic resonance spectroscopy (MRS) is a noninvasive method for measuring metabolite concentrations; however, quantitation is affected by T2 relaxation. Purpose: To estimate T2 relaxation times in pediatric brain tumors and assess how variation in T2 relaxation affects metabolite quantification. Study Type: Retrospective. Population: Twenty‐seven pediatric brain tumor patients ( n  = 17 pilocytic astrocytoma and n  = 10 medulloblastoma) and 24 age‐matched normal controls. Field Strength/Sequence: Short‐ (30 msec) and long‐echo (135 msec) single‐voxel MRS acquired at 1.5T. Assessment: T2 relaxation times were estimated by fitting signal amplitudes at two echo times to a monoexponential decay function and were used to correct metabolite concentration estimates for relaxation effects. Statistical Tests: One‐way analysis of variance (ANOVA) on ranks were used to analyze the mean T2 relaxation times and metabolite concentrations for each tissue group and paired Mann–Whitney U ‐tests were performed. Results: The mean T2 relaxation of water was measured as 181 msec, 123 msec, 90 msec, and 86 msec in pilocytic astrocytomas, medulloblastomas, basal ganglia, and white matter, respectively. The T2 of water was significantly longer in both tumor groups than normal brain ( P  < 0.001) and in pilocytic astrocytomas compared with medulloblastomas ( P  < 0.01). The choline T2 relaxation time was significantly longer in medulloblastomas compared with pilocytic astrocytomas ( P  < 0.05), while the T2 relaxation time of NAA was significantly shorter in pilocytic astrocytomas compared with normal brain ( P  < 0.001). Overall, the metabolite concentrations were underestimated by ∼22% when default T2 values were used compared with case‐specific T2 values at short echo time. The difference was reduced to 4% when individually measured water T2 s were used. Data Conclusion: Differences exist in water and metabolite T2 relaxation times for pediatric brain tumors, which lead to significant underestimation of metabolite concentrations when using default water T2 relaxation times. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:195–203.